Jidysz – angielski – polski. Problemy przekładu i pamięci - Adamczyk-Garbowska, Monika (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
The article presents selected translations of Yiddish literature into English, focusing on the influence of translator’s choices on forming the topography and realities of life in Poland before the Second World War. Elements related to material culture and multilingual quality of represented world are often eliminated or simplified. One of the main problems for translators, who usually do not know Polish, are Polish words and expressions, which are frequent in Yiddish literature written by authors of Polish extraction. Additional problems occur when Polish is used as intermediary between Yiddish and Polish. A reader who knows Eastern European realities receives an image of reality, which has been purposefully modified to facilitate reception in America, so that represented reality turns out to be more alien and exotic than in direct translation from Yiddish into Polish. This phenomenon occurs not only in fiction, but also in documentary texts, e.g. in the memorial books, which have been popular in Poland recently, and which are often translated from English intermediary texts. All this leads to important discrepancies and tensions between reality as it is imagined, remembered, and documented. Examples presented in the article come from texts by Isaac Bashevis Singer, Shalom Asch, and the Zgierz memorial book.